2007
DOI: 10.1016/j.neulet.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Sleep loss changes microRNA levels in the brain: A possible mechanism for state-dependent translational regulation

Abstract: MicroRNAs (miRNAs) are small ( approximately 22 nucleotides) non-coding RNA strands that base pair with mRNA to degrade it or inhibit its translation. Because sleep and sleep loss induce changes in many mRNA species, we hypothesized that sleep loss would also affect miRNA levels in the brain. Rats were sleep-deprived for 8h then decapitated; hippocampus, prefrontal and somatosensory cortices and hypothalamus tissues were harvested and frozen in liquid nitrogen. miRNA was extracted and then characterized using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 45 publications
4
51
0
Order By: Relevance
“…We are concerned that the present results were obtained from blood, and that these miRNAs may show different expression patterns in brain tissue. Moreover, these differences in miRNA expression may even occur among distinct brain areas (Davis et al, 2007;Kim et al, 2007). The extent of miRNA expression pattern correlation between peripheral blood and different brain structures should be evaluated in future research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are concerned that the present results were obtained from blood, and that these miRNAs may show different expression patterns in brain tissue. Moreover, these differences in miRNA expression may even occur among distinct brain areas (Davis et al, 2007;Kim et al, 2007). The extent of miRNA expression pattern correlation between peripheral blood and different brain structures should be evaluated in future research.…”
Section: Resultsmentioning
confidence: 99%
“…As an initial step of this study, a PCR array was performed with microRNAs previously reported as potentially associated with both sleep deprivation (Davis et al, 2007) and neurodegenerative disorders (Barbato et al, 2009;Eacker et al, 2009;Kim et al, 2007;Wang et al, 2008). The complete list of the 85 microRNAs used in the PCR array are indicated in Supplementary data Table 2.…”
Section: Quantitative Real Time Pcrmentioning
confidence: 99%
“…In the hypothalamus, miRNA species are both up- and downregulated after sleep deprivation [67]. Intracerebroventricular administration of a miR-132 mimetic (pre-miR-132) decreases the duration of non-rapid eye movement sleep (NREMS), while simultaneously increasing the duration of rapid eye movement sleep (REMS) during the light phase [68].…”
Section: Roles Of Mirnas In Hypothalamic Regulationmentioning
confidence: 99%
“…Also, it is possible that moderate-fold change is inherent property of miRNAs, reflecting the role of these regulators in fine tuning of expression. For example, miRNA levels after sleep deprivation in the rat's brain also show modest magnitude of fold-change (1.5-2.5: Davis et al (2007)). …”
Section: Role Of Mirna In the Circadian Clockmentioning
confidence: 99%